Sequence homogenization and chromosomal localization of VicTR-B satellites differ between closely related Vicia species - Macas, Jirí; Navrátilová, Alice; Koblízková, Andrea (Chromosoma, 2006)
Satellite sequences of the VicTR-B family are specific for the genus Vicia (Leguminosae), but their abundance varies among the species, being the highest in Vicia sativa and Vicia grandiflora. In this study, we have sequenced multiple randomly cloned VicTR-B fragments from these two species and analyzed their sequence variability, periodicity, and chromosomal localization. We have found that V. sativa VicTR-B sequences are homogeneous with respect to their nucleotide sequences and periodicity (monomers of 38 bp), whereas V. grandiflora repeats are considerably more variable, occurring in at least four distinct sequence subfamilies. Although the periodicity of 38 bp was conserved in most of the V. grandiflora sequences, one of the subfamilies was composed of higher-order repeats of 186 bp, which originated from a pentamer of the basic repeated unit. Individual VicTR-B subfamilies were preferentially located in either intercalary or subtelomeric regions of chromosomes. Interestingly, two V. grandiflora subfamilies with the highest similarity to V. sativa VicTR-B sequences were located in intercalary heterochromatic bands, showing similar chromosomal distribution as the majority of VicTR-B repeats in V. sativa. The other two V. grandiflora subfamilies showing a considerable divergence from V. sativa sequences were found to be accumulated at subtelomeric regions of V. grandiflora chromosomes.
Keywords: sekvence nukleotidů; Chromosome Mapping; konzervovaná sekvence; vikev; genetická variace; hybridizace in situ fluorescenční; Conserved Sequence; molekulární sekvence - údaje; chromozomy rostlin; Vicia; Chromosomes, Plant; DNA rostlinná; DNA, Plant; satelitní DNA; mapování chromozomů; DNA, Satellite; In Situ Hybridization, Fluorescence; Molecular Sequence Data; Base Sequence; Genetic Variation